O Jornal Oió na formação do campo literário goiano em 1957 e 1958 - Silva, Fernando Costa e (2018)
The following text is result of research involving the Oió Journal, published monthly in Goiânia between February 1957 and August 1958. It will be demonstrated that, around the Oió Journal, critics and writers met who introduced discussions involving the need to structure a literary field in Goiás. Part of these efforts, recorded in the self-titled "monthly of Goiás culture", appear to involve the professionalization of literary criticism and the prominence given to Bernardo Élis and Eli Brasiliense, most cited authors. Coordinated by the bookseller Olavo Tormin and his secretary Eliezer Penna, the Oió Journal gave an impetus to literary production in Goiás, which increased exponentially between the 50’s and 70’s. The texts published in this paper recorded the flourishing of Modernist Literature in the capital of Goiás, consolidated in the consecration of Bernardo Élis and Eli Brasiliense, in the maintenance of associations of letters, such as the Goian Academy of Letters and the Brazilian Association of Writers, and in the systematization of criticism professional.